The Design of Basic Computer Neworking Simulation Learning using Multimedia Development Life Cycle Method based on Augmented Reality at SMKN 1 Tangerang - Dram Renaldi; Elza Satrio Aziz (Tech-E, 2021)
Augmented Reality has entered technology trends in all fields, both marketing and education, Augmented Reality media also requires users to be comfortable when interacting. SMKN 1 Tangerang organizes a distance education system with various methods, in this case the subject which is Basic Computer Networks uses mobile-based learning simulations with Augmented Reality which aims to develop students' abilities in the world of networked computers independently. This system also requires a user experience and user interface development method, namely Luther's Multimedia Development Life Cycle model because it has six stages, namely concept, design, data collection, merging, testing, and distribution, resulting in interactive applications.